Efficacy and tolerability of zolmitriptan oro-dispersible wafer in treatment of childhood migraine. Issue 2 (18th October 2013) - Kerrison, Caroline; Wright, Francesca; Piper, Joseph; Kumar, Ram; Hawcutt, Daniel B
Abstract : Introduction: Migraine affects 8% of children, and may require pharmacological therapy to control symptoms. Current acute treatments include (5-Hydroxytryptamine Receptor 1 (5-HT1 ) receptor agonists, although the only licensed medication for paediatric patients in this class in the UK is intranasal sumatriptan. Oro-dispersible wafers of zolmitriptan are used in practice but have not been evaluated in the paediatric setting. Methods: A prospective case note audit of oro-dispersible zolmitriptan wafers use in the treatment of paediatric migraine by a consultant paediatric neurologist was carried out. Results: Symptomatic benefit was noted in 71.4% (n=10) of patients who have been prescribed the oro-dispersible wafer formulation. All subgroups of migraine included in the audit had some participants who benefitted from the medication. Five patients (35.7%) complained of mild adverse effects: nausea (n=2, 14.3%); Somnolence (n=2, 14.3%); Tingling sensation on the tongue (n=1, 7.1%). No patients had any severe adverse effects. Conclusions: In children with migraine treated in a tertiary paediatric neurology setting, the oro-dispersible wafer formulation of zolmitriptan is effective and well tolerated. Adequately powered prospective studies are required to determine the optimal place for this medication in paediatric migraine management.